Cerebral aspergillosis in a patient on ibrutinib therapy—A predisposition not to overlook. (September 2019) - Faisal, Muhammad Salman; Shaikh, Hira; Khattab, Ahmed; Albrethsen, Mary; Fazal, Salman
Ibrutinib has revolutionized the treatment of B-cell malignancies since its approval for chronic lymphocytic leukemia. It is also used in mantle cell lymphoma, diffuse large B-cell lymphoma, Waldenstrom's macroglobulinemia, among others. It is a Bruton's tyrosine kinase inhibitor that acts on B-cell receptor signaling pathway and predisposes to various infections due to its effects on neutrophils, monocytes and T cells. We present a case of cerebral invasive aspergillosis in a patient being treated with ibrutinib for relapsed chronic lymphocytic leukemia. It was hard to associate the condition to ibrutinib versus the chronic lymphocytic leukemia. The patient was successfully treated with a combination of voriconazole and micafungin, resulting in complete recovery and no residual deficits. This highlights the importance of recognizing the rare complication in those on ibrutinib and initiating the treatment immediately with appropriate antifungal agents to improve prognosis of this potentially fatal condition.